Social presence and self-focused attention of persistence of UPV Social Science students how to accomplish an impossible task? - Fajardo, Josephine U.
The experiment employed a sample of 40 UPV Social Sciences students. And parallel to Robert Zajonc's (1965) classical view on social facilitation-inhibition effects, the presence of unpredictable mixed-sex audiences inhibited persistence in the unsolvable tangrams puzzle. Moreover, the inhibitory effect of self-focused attention was established as participants who were induced to actively introspect exhibited persistence inhibition comparable to that incited by social presence. Furthermore, an interaction was observed accounting for the greater persistence inhibition when both factors were presented. Lastly, the participants' sex did not regulate persistence. Hence, the results indirectly negate Allport's (1924) endorsement of more collectivist approaches in social psychology. And nor did it support the researcher's presumption that females would exhibit greater persistence in a heterogeneous group